UTILIZATION OF MOBILE LEARNING MEDIA AS A CIVICS LEARNING RESOURCE IN IMPROVING UNDERSTANDING OF TEACHING MATERIALS - Lilis Rosita; Ana Maulana; Prima Melati (Journal Civics And Social Studies, 2022)
PKn is one of the subjects that are still considered saturated, less interested so that it affects the level of understanding of the teaching material. It needs a touch of technology as a supporting capacity so that PKn learning is more interesting and easier to understand. The use of Mobile learning media is considered effective to convey the message of PKn learning in order to improve understanding of teaching materials. It needs research on (1) how the use of media as a source of learning civics, (2) how the understanding of students in learning civics, (3) how the use of mobile learning media as a source of learning civics can improve understanding of teaching materials. From the analysis of hypothesis test data. There is a significant increase, the use of mobile learning media as a source of learning for Civics in improving understanding of teaching materials. Correlation coefficient test has a significant relationship with (r) = 0.773, the degree of relationship between the two variables “strong”, coefficient of determination (d) = 77%, the remaining 23% is influenced by other variables. The results of the study concluded that, mobile learning media as a source of Pkn learning, can improve understanding of teaching materials. The study was conducted on XII grade students at SMAN 29 Garut. The recommendation of the research is expected that teachers can utilize various learning media to improve students ' understanding of teaching materials.